Synthesis and spectral characterization of new azodyederived from benzimidazole and its complexation with selected transition metal ions. - Kadhim, Khalid Jawad; Hatem, Ban A. (JOURNAL OF ADVANCES IN CHEMISTRY, 2015)
The preparation and spectral characterization of new ligand containing benzimidazole as organic heterocyclic azo dye compound 2-[6-(benzimidazolyl)azo]-2,4-di chloro phenol (BIADClP) was prepared by coupling reaction benzimidazole diazonium chloride with 2,4-di chloro phenol in alkaline alcoholic solution. The structure of azo dye ligand has been characterize by spectral studies such as 1H-NMR ,mass spectrum ,FT-IR, UV-Visb. and element analysis. New six complexes with Co(II), Ni(II), Cu(II), Zn(II), Cd(II) and Hg(II) ions were prepared and identification by several physiochemical techniques; such as C.H.N element, magnatic susceptibility, atomic absorption, molar conductivity, IR and electronic spectra. The used techniques showed the formation of all complexes 1:2 [M:L] complexes and suggested octahedral geometry with d2sp3 hybridization of Co(III) and sp3d2 with residule chelat complexes.The coordination number of the metal ion is found to be six with binding through the phenolate O, azo N3 and with the imidazole N3 atom.All complexes that non electrolyte and no conductive species excepted the Co(III)-complexes is 1:1 electrolyte